2016
DOI: 10.1016/j.jaim.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenging and gastroprotective activity of methanolic extract of Gmelina arborea stem bark

Abstract: BackgroundGmelina arborea (GA) is widely used in traditional medicine for treating a number of ailments including gastrointestinal tract disorders.ObjectiveTo evaluate the gastroprotective effect of GA stem bark against ethanol-induced gastric ulcer in Wistar rats.Materials and methodsAll animals were fasted for 36 h and received GA extract 250 and 500 mg/kg body weight (bw), 1 h before the administration of ethanol. The animals received ranitidine 50 mg/kg bw which served as the standard. The rats were sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Neutrophils are recruited to the site of injury lead to ROS production that results in oxidative stress to mucosal cells and ulcer. Therefore, the use of antioxidants might be helpful in protecting the mucosal cells from oxidative damage and speeding up the healing process [12]. The constituents of Lavandula stoechas L. include camphor, linalool, linalyl acetate, 1-8 cineole and γterpinene while its antioxidant potential is found to be comparable with vitamin E as reported in previous studies [13].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Neutrophils are recruited to the site of injury lead to ROS production that results in oxidative stress to mucosal cells and ulcer. Therefore, the use of antioxidants might be helpful in protecting the mucosal cells from oxidative damage and speeding up the healing process [12]. The constituents of Lavandula stoechas L. include camphor, linalool, linalyl acetate, 1-8 cineole and γterpinene while its antioxidant potential is found to be comparable with vitamin E as reported in previous studies [13].…”
Section: Introductionsupporting
confidence: 58%
“…The exact mechanism how ethanol causes gastric lesions is not fully understood [9, 10] however, ethanol is reported to produce a disturbance in gastric mucosal barrier via exfoliation of cells [11,35] followed by the recruitment of inflammatory cells to the site of injury and production of reactive oxygen species (ROS). As ROS and other mediators of inflammation may lead to oxidative damage [12,36] therefore, by scavenging free radicals, antioxidants might prove as useful gastroprotective agents. In the present study, both the aqueous and methanolic Lavandula stoechas L. extracts showed strong free radical scavenging activity as determined by DPPH method (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reduction in MDA levels were reported in the treated rats with several compounds, such as 3-(2-Chlorophenyl)-1-phenyl-propenone and Zn(II)–curcumin complex [51, 52]. It is reported that ROS, such as hydroxyl radicals, superoxide anions, and lipid peroxides are harmful species which is known to provoke gastric ulcer development [53]. Free radical ultimately causes depletion in tissue antioxidant status leading to lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of methanol extract of G. arborea and its fractions can be attributed to the presence of the flavonoid [8] present therein. Moreover, the insecticidal activity of G. arborea extracts against Megalurothrips sjostedti [9] and Callosobruchus chinensis and Sitophilus oryzae [10], would healing effects [11], anti-ulcer potentials [12] and antiangiogenic activity [13] have been reported. It was also reported that an ethanolic leaf extract of G. arborea has potent in vitro cytotoxic activity against colon cancer (COLO 201), gastric cancer (HT-29) and human oesophagel cancer (TE-2) cell lines [14].…”
Section: Introductionmentioning
confidence: 99%